Pemberdayaan Peternak Sapi Potong Menuju Kemandirian - Lany Sonia Wulandari; Sri Subekti (Fakultas Pertanian Universitas Jember, 2020)
Empowerment is needed to support the selfreliance and progress of beef cattle farmers so that beef cattle farmers can develop. The selfreliance of beef cattle farmers through livestock gapoktan has a role to help the progress of farmers in the form of feed concentrates and modern technologies such as life scales and feed making machines in developing their businesses. This study aims to determine the empowerment of beef cattle farmers through livestock gapoktan in Karanganyar Village, Tegalampel District, Bondowoso Regency. Location selection was determined purposively (purposive method), with the reason that there was an advanced and largest livestock gapoktan in Bondowoso District. The research conducted is qualitative research with data analysis using the method of Miles and Huberman analysis and the determination of informants using purposive sampling. The results showed that the empowerment of farmers can be seen from three things, namely voice, choice (rational choice), which is able to increase selfreliance. Voice is the voice of beef cattle breeders who are able and courageous to convey the aspirations of farmers to progress, the need for raising livestock, giving ideas or ideas, conveying interests and demands in performance in livestock gapoktan. In a rational choice, farmers are brave enough to choose rationally in raising cattle and join with livestock gapoktan based on their goals and values ​​and take action so that the goals can be achieved. The ability of beef cattle farmers to deliver their voices and make rational choices is a process of increasing selfreliance. The selfreliance of cattle breeders can be seen as the ability of farmers to fulfill their daily needs, collaborate and think sustainably. Keywords: empowerment, voice, choice, selfrelience